Adult medulloblastoma momprises three major molecular variants - Remke, Marc; Hielscher, Thomas; Northcott, Paul A.; Witt, Hendrik; Ryzhova, Marina; Wittmann, Andrea; Benner, Axel; Deimling, Andreas von; Scheurlen, Wolfram; Perry, Arie; Croul, Sidney; Kulozik, Andreas; et al. (Journal of clinical oncology, 2011)
Purpose - - Medulloblastoma is a rare primary brain tumor in adults, whereas it constitutes the most common malignant brain tumor in children. Integrated genomics approaches revealed at least four distinct disease variants in children. The aim of this study was to investigate molecular subtypes and their prognostic implication in a large cohort of adult medulloblastomas as the biology in this age group remains poorly understood. - - Patients and Methods - - We combined transcriptome and DNA copy number analyses for 28 adult medulloblastomas. Statistical and bioinformatic tools were applied to discover distinct molecular variants. Clinical and molecular characteristics of each biologic subtype were validated using immunohistochemistry on a tissue microarray derived from an independent patient cohort of adult medulloblastomas (n = 103). - - Results - - Gene expression profiles revealed three distinct molecular variants with stable subtype separation using the 300 most varying transcripts. Distinct demographics, genetics, transcriptome, and prognosis were noted for each subtype of adult medulloblastoma. Immunohistochemistry revealed aberrant activation of the sonic hedgehog (SHH) pathway in over half of adult medulloblastomas constituting a promising molecular therapeutic target. In contrast, subtype C tumors, which comprise a robust subtype in childhood medulloblastoma are only exceptionally seen in adult cohorts. Notably, adult subtype D and Wnt/wingless tumors were associated with worse prognosis than pediatric cohorts, whereas survival for SHH tumors was similar for both age groups. - - Conclusion - - The transcriptome of adult medulloblastomas differs considerably from pediatric counterparts, both in terms of tumor biology and prognostic impact. Therefore, age-specific classification is required and must be adapted for use in clinical trials of adult medulloblastoma.